Approach to Secondary Adult Basic Education multiliteracy: making a human rights slideshow from the novel Le Ventre de l’Atlantique - Cabornero, Eduardo; García Parejo, Isabel (Didáctica. Lengua y Literatura, 2012)
This article describes a teaching sequence developed by adult basic education teachers and students in Madrid. The aim was to design and develop a slideshow based on the theme of the Human rights. The ultimate goal was to exhibit the slideshow so that a dialogue could be established among those present based on the reality described in it. We suggest that, insofar as the slideshow not only involves reading and writing in different codes but also requires the collaboration of teachers from all areas of knowledge, this teaching experience is of much interest for the development of diverse communicative skills.